Interactive Multimedia Engine Management System (EMS) to Improve Prior Knowledge and Problems Solving Ability - Komarudin Komarudin; Ahmat Mukhadis (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
There are three problems in teaching engineering, especially in the field of electricity, those are: (1) students are unable to read electricity wiring; (2) students do not understand the basic concepts of electricity; (3) students do not understand the basic concept of the relationship between the electrical components. The purpose of this article are: (1) to describe multimedia, especially interactive multimedia engine management systems, prior knowledge, problem-solving; (2) to describe the relationship between interactive multimedia and prior knowledge; (3) to describe the relationship between interactive multimedia and problem solving; and (4) to provide the concept of interactive multimedia engine management system. The collection of information in this article uses a literature review or library research. Problem-solving is an attempt to solve problems through high-level thinking (high order thinking). Prior knowledge is the initial knowledge students have when entering topics with the same background. The existence of interactive multimedia or multimedia has a positive impact on prior knowledge. Some interactive multimedia research has a positive impact on the ability of problem-solving.